Psychological Capital: a foundational construct in positive organizational psychology - Cabezas Corcione, Andrés (2019)
The present article aims to raise awareness of the importance of the psychological capital as a fundamentalconstruct within the positive organizational psychology. It maintains and demonstrates its positive impact on jobperformance, as well as happiness and life satisfaction of workers. For this it will be briefly reviewed what ismeant by positive organizational psychology, so that a conceptual definition of the CaPsi and its four dimensions;hope, resilience, optimism and self-efficacy, can be performed. It concludes that this construct meets the fivecriteria of inclusion, proposed by Youssef, Luthans & Avolio in the year 2007, which allows the study andapplication of the skills and strengths that can be measured and developed to improve performance (Nelson andCooper, 2007). The article emphasizes that despite the few studies that have been conducted so far, the resultsshowed highly significant relationships between psychological capital and job performance, and clarifies that theinstruments used in each investigation, have shown high validity and reliability